Pemanfaatan Media Kahoots sebagai Motivasi Belajar Mengikuti Kuis Wacana Bahasa Indonesia - Charlina, Charlina; Septyanti, Elvrin (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
Quiz is one of the assessment items that can be addressed to the students. Technological development helps its distribution and assessment quickly. One of the media that can be used is called kahoots. Through the utilization of kahoots, it can be described the students’ motivation in learning to take the Indonesian language discourse quiz. Descriptive qualitative method was used in this research. The sample of this study was 2017A batch of students with 34 participants. This study used a motivational questionnaire that was made in the form of a checklist with an assessment range of 1 to 5 to describe students' learning motivation in taking quizzes related to Indonesian discourse theory. After collecting the data, 30% of the lower group was calssified as a learning group that had a low level of motivation, meanwhile, 30% of the upper group was categorized as a group that had a high level of motivation. In analyzing the data, this study followed the stages which were identifying, changing the value of categories into assessment scores and analyzing. The result of the research showed that students was highly motivated in taking the Indonesian language discourse quiz by applying kahoots and it was proven by a score which was 86%.